Comfort with courtyards in Dhaka apartments - Ali, Zainab Faruqi (BRAC University, 2010)
The building activities in the residential arena of Dhaka are primarily involved in mid to high rise apartments of various sizes and styles in almost every available space. The majority of these, mostly six storied, are compact type buildings with no courtyards inside. Hence there is a lack of natural ventilation and daylight in the interior spaces, which affect the level of indoor comfort. The age-old methods of designing in the context have proven that providing natural ventilation is an important strategy for having comfort. The traditional residences, rural or urban, with interior courtyards created a living condition that was and still is, environmentally, functionally, and socially sustainable. The author, through studying a number of residential buildings both with and without courtyards, stresses that introduction of this important environmental element, or the courtyard in the contemporary apartment buildings can provide much better indoor comfort in terms of light, air and coolness. The study is a synthesis of recorded temperatures, questionnaire survey and observations made on various aspects of the plan, section, form, materials and impact of the presence or absence of courtyards. The author also suggests that considering 'value-for-money' factor, new building regulations of floor area ratio, and above all indoor comfort the scope of applying courtyards in residential apartments for good thermal and luminous environment is still possible.